Reversal of sorafenib resistance in hepatocellular carcinoma by curcumol: insights from network pharmacology, molecular docking, and experimental validation - Zhang, Ni; Tian, Xinchen; Liu, Fen; Jin, Xiaohan; Zhang, Jiaqi; Hao, Lingli; Jiang, Shulong; Liu, Qingbin (Frontiers in Pharmacology, 2025)
BackgroundCurcumol, a bioactive sesquiterpenoid extracted from traditional Chinese medicine (TCM), has demonstrated potential in overcoming tumor drug resistance. However, its mechanisms in reversing drug resistance, particularly in hepatocellular carcinoma (HCC) resistant to sorafenib, are not yet fully elucidated. This study aims to explore the molecular mechanisms by which curcumol reverses sorafenib resistance in HCC using a combination of network pharmacology, molecular docking, and in vivo and in vitro experiments.MethodsWe identified curcumol targets and genes associated with sorafenib-resistant HCC, resulting in a set of overlapping targets. These intersection targets underwent enrichment analysis using DAVID, and a protein-protein interaction (PPI) network was constructed via the STRING database and Cytoscape. Molecular docking confirmed the binding of curcumol to core targets. In vitro assays, including CCK-8, colony formation assay, apoptosis detection, wound healing, and Transwell assays, evaluated curcumol’s effects on sorafenib-resistant HCC cells. Western blotting assessed the impact on PI3K/AKT and JAK/STAT3 signaling pathways. Additionally, a sorafenib-resistant HCC xenograft mouse model was established to observe the in vivo efficacy of curcumol combined with sorafenib.ResultsWe identified 117 potential targets for curcumol in reversing sorafenib resistance in HCC. Among them, five core targets—ALB, STAT3, HSP90AA1, HSP90AB1, and SRC—showed strong binding affinity with curcumol. KEGG pathway analysis of the intersecting genes highlighted significant involvement of the PI3K/AKT, JAK/STAT3, Ras, Rap1, HIF-1, FoxO, and mTOR signaling pathways. In vitro experiments revealed that curcumol significantly enhanced the sensitivity of sorafenib-resistant HCC cells to sorafenib, inhibiting cell proliferation, invasion, and migration while promoting apoptosis. In vivo studies further confirmed that curcumol combined with sorafenib effectively inhibited tumor growth in sorafenib-resistant HCC models.ConclusionThis study provides compelling evidence that curcumol can reverse sorafenib resistance in HCC by modulating multiple signaling pathways, including PI3K/AKT and JAK/STAT3 pathways. Our findings suggest that curcumol holds promise as a novel therapeutic agent for overcoming drug resistance in HCC, offering a new avenue for clinical intervention.